Phase behavior and hydrocarbons distribution in shale oil during EOR with nano-confinement effect - Wang, Yuanzheng; Cao, Renyi; Jia, Zhihao; Huang, Tao; Jia, Pin; Cheng, Linsong; Duan, Wenhao; Sun, Zhaole (Frontiers in Energy Research, 2023)
The phase behavior of fluids in shale oil reservoirs during enhanced oil recovery (EOR) process becomes more complex. To address this, we modify the Peng-Robinson equation of state (PR-EOS) and establish a pore-size dependent correlation to describe fluid phase behavior in nanopores. Using MATLAB programming, we compile a vapor-liquid equilibrium calculation module that considers the shift of critical parameters and the gas-liquid capillary pressure to simulate the phase behaviors of two different composition shale oil samples. We then verify the reliability of this method by perfectly matching commercial software tNavigator PVTi using published data. Our results show that fluids in nanoscale pores are more likely to exhibit near-critical or condensate states. We also compare the changes in phase behavior when fluids dissolve CO2 and CH4 and observe the phase transition (from gaseous to liquid phase) of the lighter crude oil sample that dissolved more gas during differential liberation experiment (DL).Finally, we use CO2 pre-pad energized fracturing of a shale oil reservoir in northern China as an example to explain abnormal production performances, such as a majority of light hydrocarbons in the produced fluid of the well during the flow back stage, single gas phase production in the early production stage, and stable gas/oil ratio (GOR) in the process of development. Our novel methodology and phase behavior change mechanism can enhance our understanding of the phase behavior of fluids in shale oil reservoirs during enhanced oil recovery.